2010
DOI: 10.1016/j.jacc.2009.11.091
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early, Pre-Hospital Initiation of High Bolus Dose Tirofiban in Patients With ST-Segment Elevation Myocardial Infarction on Short- and Long-Term Clinical Outcome

Abstract: Early, pre-hospital initiation of HBD tirofiban, in addition to high-dose clopidogrel, improves the clinical outcome after primary percutaneous coronary intervention in patients with STEMI. (Ongoing 2b/3a inhibition In Myocardial infarction Evaluation; ISRCTN06195297).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(53 citation statements)
references
References 19 publications
2
51
0
Order By: Relevance
“…Analogues to our findings may be drawn to the experience with use of the glycoprotein IIb/IIIa inhibitor tirofiban for patients with STEMI, for which pretreatment with tirofiban may confer cardioprotective effects27 and improve clinical outcome 28. Notably, a post-hoc subanalysis demonstrated that the highest efficacy of tirofiban treatment was seen in patients with long healthcare system delays and tirofiban pretreatment time 29.…”
Section: Discussionsupporting
confidence: 70%
“…Analogues to our findings may be drawn to the experience with use of the glycoprotein IIb/IIIa inhibitor tirofiban for patients with STEMI, for which pretreatment with tirofiban may confer cardioprotective effects27 and improve clinical outcome 28. Notably, a post-hoc subanalysis demonstrated that the highest efficacy of tirofiban treatment was seen in patients with long healthcare system delays and tirofiban pretreatment time 29.…”
Section: Discussionsupporting
confidence: 70%
“…We have previously reported the long-term clinical outcomes benefit of a GPI-facilitated PCI strategy7; however, in this current analysis we provide further insight, showing that a high-risk subset of patients, as identified by higher levels of NT-proBNP upon presentation (figure 1), represents a subgroup who derives particular benefit from early GPI treatment in terms of significant mortality reduction up to 1 year (figure 2). This lower mortality rate was maintained up to 5 years, although at this point with a non-significant difference probably because other factors may influence very long-term outcomes.…”
Section: Discussionmentioning
confidence: 57%
“…Similarly, in the Intracoronary Eptifibatide (ICE) Trial, the intracoronary bolus administration of eptifibatide during PCI in patients with acute coronary syndromes resulted in higher local platelet glycoprotein IIb/IIIa recept or occupancy, which was associated with improved microvascular perfusion demonstrated by an improved corrected TIMI Frame Count [9].…”
Section: Intracoronary Gp Iib/iiia Inhibitorsmentioning
confidence: 99%